Media optimization of antimicrobial activity production and beta-glucan content of endophytic fungi Xylaria sp. BCC 1067 - Jayasekara, L. A.Channa Bhathiya; Poonsawad, Attaporn; Watchaputi, Kwanrutai; Wattanachaisaereekul, Songsak; Soontorngun, Nitnipa (My University, 2022)
Fungi is a notable asset for drug discovery and production of pharmaceuticals; however, slow growth and poor product yields have hindered industrial utilization. Here, the mycelial biomass of Xylaria sp. BCC 1067 was examined in parallel with the assessment of antimicrobial properties by using media-type selection. To enhance both mycelial content and antifungal activity, the media replacement approach was successfully applied to stimulate fungal growth and successively switched to poorer malt-peptone extract media for metabolite production. This simple optimization reduced fungal cultivation time by 7 days and yielded 4-fold increased mycelial mass (32.59 g/L), with approximately 3-fold increased antifungal activity against the model yeast Saccharomyces cerevisiae strain. A high level of β-glucan (115.84 mg/g of cell dry weight) and additive antibacterial effect against Propionibacterium acnes were also reported. This simple strategy of culture media optimization allows for investigation of novel and rich source of health-promoting substances for effective microbial utilization.
Keywords: Antimicrobial; Media optimization; Microbial biotechnology; Natural bioactive product; Xylaria sp